2012
DOI: 10.1097/nur.0b013e31825aebab
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Central Line–Associated Bloodstream Infection Bundle

Abstract: Clinical nurse specialist surveillance, management, and leadership following project implementation are valuable strategies for continued optimal patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Magnet Recognition Program is a prestigious designation by the American Nurses Credentialing Center for hospitals that demonstrate excellence in nursing care and outcomes through clinical nurses. CNSs are integral in the implementation of evidence-based practice, research, and quality initiatives (4, 17, 35, 36). Successful designation requires access to clinical experts and resources to facilitate those activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnet Recognition Program is a prestigious designation by the American Nurses Credentialing Center for hospitals that demonstrate excellence in nursing care and outcomes through clinical nurses. CNSs are integral in the implementation of evidence-based practice, research, and quality initiatives (4, 17, 35, 36). Successful designation requires access to clinical experts and resources to facilitate those activities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fabbruzzo-Cota et al (7) reported CNS-led HAPI reduction efforts were associated with an 80% reduction in HAPIs over a 1-year period with a rate reduction from 0.24% to 0.08% in the first 3 months. In 2012, Richardson and Tjoelker (17) reported a 2.5-year, CNS-led CLABSI reduction initiative that prevented eight CLABSIs, which yielded $200,000 in cost avoidance and saved 1.4 lives. Similarly, Colwill et al (19) identified an association with CNS involvement in care and a reduction in CAUTI rates in the critical care setting.…”
Section: Cns Practice and Contributions To Outcomesmentioning
confidence: 99%
“…Another important resource in the translation process is the use of clinical leaders or experts to advance the process. Tuite and George () and Richardson and Tjoelker () used clinical nurse specialists to facilitate clinical change. Others have stressed that it is important to create a community of practice or a network of practitioners who can act as knowledge brokers (Gagnon, ; Shea, ) and who can develop active collaborations between researchers and clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed a paucity of studies investigating patient self-reported central venous catheter care practices. Several studies in the literature reveal data on the knowledge, attitudes, compliance with procedures, and evidence-based practices in the prevention of CRBSIs by healthcare workers (Beathard and Urbanes, 2008; Kallen et al, 2010b; Morrison, 2012; Richardson and Tjoelker 2012; Bianco et al, 2012). An investigation of hospital-wide compliance with central venous catheter dressing recommendations revealed that deficiencies were present in 31% of the dressings monitored (Rupp et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of hospital-wide compliance with central venous catheter dressing recommendations revealed that deficiencies were present in 31% of the dressings monitored (Rupp et al, 2012). Richardson and Tjoelker (2012) described the value and role of a clinical nurse specialist as the team leader directing national guidelines and interdisciplinary implementation of strategies to decrease CRBSIs. Morrison (2012) investigated the lived experience of nurses providing central line dressing changes and care.…”
Section: Introductionmentioning
confidence: 99%